Assessment of Post-Myocardial Infarction Lipid Levels and Management - Muhammad Waqas; Imran Ellahi Soomro; Bilal Akhtar; Shah Nawaz Panhwar; Abdul Mueed; M Tahseen Raza, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: One of the major causes of death worldwide includes acute myocardial infarction (AMI) which is a type of heart attack. Whenever a person faces AMI, it becomes important for that person to carefully manage their cholesterol levels so that they can prevent any other heart problem or another heart attack. Therefore, it is necessary for heart patients to reduce their LDL-C levels (low-density lipoprotein cholesterol) because acute coronary events are caused due to high LDL-C. As recommended by 2021 European Society of Cardiology, LDL-C levels should be lowered by 50% after an event which means it should be below 1.4 mmol/L. Objective: To assess the management of lipid profiles and lipid levels in patients after having myocardial infarction Study design: A cross-sectional study Duration and place of study: This study was conducted in Peoples University of Medical and Health Sciences for Women Shaheed Benazirabad Nawabshah from october 2023 to october 2024 Methodology: This is a cross-sectional study which was performed in the cardiology outpatient clinic of the hospital. This study included all the patients who had gone through their first acute coronary event in the last 3 years. All the participants of this study were aged at least 18 years and above. This research followed the 2021 ESC guidelines in order to prevent cardiovascular disease. Patients were advised to follow-up 6 weeks after their first visit. For cases where individuals couldn’t tolerate statins or did not reach the recommended LDL-C levels, other lipid lowering medicines were added as suggested by the guidelines. T-tests and chi-square tests were conducted. SPSS version 21 was used. Results: There were a total of 150 individuals who were a part of this study. Among these patients, the majority of them were males (70.6%). All the participants of this study were aged at least 18 years and above. The average age calculated was 57.1 years. The average time since the first acute coronary event was 36 months. The majority of the participants were on a recommended dose (n=132). Conclusion: Although the majority of the participants were regularly following the statin treatment, achieving the target lipid levels is still a challenge.